Variations de l'élaboration conceptuelle dans différentes modalités d'enseignement bilingue - Grobet, Anne; Vuksanovic, Ivana (My University, 2017)
This paper examines the relationship between programmed and emergent aspects of knowledge construction in bilingual education, through the analysis of conceptual networks of subject content. More precisely, the focus is on classroom interaction sequences in which participants (teacher and students) are working on definitions of certain phenomena or discussing different notions and concepts. These concepts have a common conceptual structure and build up conceptual networks that reflect the paradigm of different subject disciplines (for example, chemistry, biology, law, etc.), but do not have the same relevance for the knowledge construction and acquisition process. By comparing conceptual structures of subject content with different modalities of classroom interaction in which they occur, we examine the degree of their relevance and their role in the knowledge construction process. In this way, we are trying to find out which conditions could emphasize the occurrence of non-programmed notions and what is the impact of code-switching and meta-linguistic activities on it.
Keywords: bilingual education; conceptual network; metadiscourse; linguistic knowledge; subject knowledge